Democracy and institutional quality: Theory and Evidence - Tommy Krieger (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We present a simple model that illustrates how democracy may improve the quality of economic institutions. The model further suggests that institutional quality varies more across autocracies than across democracy and that the positive effect of democracy on institutional quality is increasing in people's human capital. Using a new panel data set, covering 140 countries and the period from 1920 to 2015, and different measures of institutional quality, we present results from fixed effect and two-stage least squares regressions that confirm the predictions of our model.
Keywords: D73; H11; O43; P14; P48; 330; Democracy; Development; Economic Institutions; Human Capital; Institutional Quality; Political Economy; Political Transitions; Private Property Rights